Malnutrition and Risk of Procedural Complications in Patients With Atrial Fibrillation Undergoing Catheter Ablation - Kim, Daehoon; Shim, Jaemin; Kim, Yun Gi; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Choi, Jong-Il; Joung, Boyoung; Lee, Moon-Hyoung; Kim, Young-Hoon; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2021)
Background: Little is known about the prognostic value of nutritional status among patients undergoing atrial fibrillation (AF) catheter ablation (AFCA). We compared the risk of procedure-related complications and long-term rhythm outcomes of AFCA according to nutritional status. Methods: We included 3,239 patients undergoing de novo AFCA in 2009-2020. Nutritional status was assessed using the controlling nutritional status (CONUT) score. The association between malnutrition and the risk of AFCA complications or long-term rhythm outcomes was evaluated. We validated the effects of malnutrition using an external cohort of 360 patients undergoing AFCA in 2013-2016. Results: In the study population (26.8% women, median age: 58 years), 1,005 (31.0%) had malnutrition (CONUT scores ≥2); 991 (30.6%) had mild (CONUT 2–4) and 14 (0.4%) had moderate-to-severe (CONUT ≥5) malnutrition. The overall complication rates after AFCA were 3.3% for normal nutrition, 4.2% for mild malnutrition, and 21.4% for moderate-to-severe malnutrition. Moderate-to-severe malnutrition (odds ratio [OR] 6.456, 95% confidence interval [CI] 1.637-25.463, compared with normal nutrition), older age (OR 1.020 per 1-year increase, 95% CI 1.001-1.039), female sex (OR 1.915, 95% CI (1.302-2.817), and higher systolic blood pressure (OR 1.013 per 1-mmHg increase, 95% CI 1.000-1.026) were independent predictors for the occurrence of complications. In the validation cohort, malnutrition (CONUT ≥2) was associated with a 2.87-fold higher risk of AFCA complications (95% CI 1.174-7.033). The association between malnutrition and a higher risk of AFCA complications was consistently observed regardless of body mass index and sex. Malnutrition did not affect rhythm outcomes during the median follow-up of 40 months (clinical recurrence: 37.0% in normal nutrition versus 36.5% in malnutrition). Conclusion: Malnutrition, which is common in patients undergoing AFCA, was associated with a substantially higher risk for complications after AFCA.